The world bank annual report 2009 year in review. - The World Bankk (Washington, DC The World Bank, 2009)
The Annual Report is prepared by the Executive Directors of the International Bank for Reconstruction and Development (IBRD) and the International Development Association (IDA)?collectively known as the World Bank?in accordance with the by-laws of the two institutions. The President of the IBRD and IDA and the Chairman of the Board of Executive Directors submits the Report, together with the accompanying administrative budgets and audited financial statements, to the Board of Governors.
The World Bank Annual Report 2009, Year in Review, explores the impact of the global financial and economic crisis in developing countries, and fast-track funding and programs that can help member countries withstand the debacle. In addition, new and ongoing programs and projects in health, climate change, infrastructure, and several other areas are highlighted. A new feature this year is personal-impact stories for each region, relaying the positive effects of World Bank assistance on individuals.
Keywords: Finance; Business and economics; Banks and banking